A Study of Superconducting Transformer with Short-Circuit Current Limitation - V.Z. Manusov; D.A. Pavlyuchenko; J.S. Ahyoev (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The paper presents physico-mathematical models for analyzing transient processes in electrical networks having transformers with a high temperature superconducting winding. One of the main purposes of the study is the investigation of the short circuit current limitation process with the use of a transformer with a high temperature superconducting winding, that allows the combination of two series-connected elements, transformer and reactor, in one device. The efficiency of this method for short circuit current limitation is provided by the fact that the critical value of superconducting winding temperature is exceeded under short circuit current flowing, then it passes into the normal state with a high impedance winding, thus limiting a short circuit current. It is important to know the moment when superconducting material passes into the normal state with the loss of superconductivity. For this purpose, the program for calculating the quantity of heat under short circuit current flowing before its interruption was developed. If a 40 MVA transformer with a high temperature superconducting winding is considered, short circuit should be cleared after 100 ms without transformer disconnection. It is proposed to use a hybrid winding in addition to the main winding for short circuit current limitation. Conducted investigations showed that the return of a winding into the superconducting state depends primarily on the ratio between a short circuit current and a rated load current. This represents the criterion for returning or not returning into the superconducting state for transformer windings.